Total Antioxidant Capacity and Its Dietary Sources and Seasonal Variability in Diets of Women with Different Physical Activity Levels - Człapka-Matyasik Magdalena; Ast Katarzyna (Polish Journal of Food and Nutrition Sciences)
Increased physical activity induces oxidative stress and utilization of dietary antioxidants. Information on dietary sources of antioxidants in diets are limited.